Identifying challenges to implementation of clinical practice guidelines for sentinel lymph node biopsy in patients with melanoma in Australia: protocol paper for a mixed methods study. Issue 2 (27th February 2020) - Rapport, Frances; Smith, Andrea L; Cust, Anne E; Mann, Graham J; Watts, Caroline G; Gyorki, David E; Henderson, Michael; Hong, Angela M; Kelly, John W; Long, Georgina V; Mar, Victoria J; Morton, Rachael L; et al.
Abstract : Introduction: Sentinel lymph node biopsy (SLNB) is a diagnostic procedure developed in the 1990s. It is currently used to stage patients with primary cutaneous melanoma, provide prognostic information and guide management. The Australian Clinical Practice Guidelines state that SLNB should be considered for patients with cutaneous melanoma >1 mm in thickness (or >0.8 mm with high-risk pathology features). Until recently, sentinel lymph node (SLN) status was used to identify patients who might benefit from a completion lymph node dissection, a procedure that is no longer routinely recommended. SLN status is now also being used to identify patients who might benefit from systemic adjuvant therapies such as anti-programmed cell death 1 (PD1) checkpoint inhibitor immunotherapy or BRAF-directed molecular targeted therapy, treatments that have significantly improved relapse-free survival for patients with resected stage III melanoma and improved overall survival of patients with unresectable stage III and stage IV melanoma. Australian and international data indicate that approximately half of eligible patients receive an SLNB. Methods and analysis: This mixed-methods study seeks to understand the structural, contextual and cultural factors affecting implementation of the SLNB guidelines. Data collection will include: (1) cross-sectional questionnaires and semistructured interviews with general practitioners and dermatologists; (2) semistructured interviews with other healthcare professionals involved in the diagnosis and early definitive care of melanoma patients and key stakeholders including researchers, representatives of professional colleges, training organisations and consumer melanoma groups; and (3) documentary analysis of documents from government, health services and non-government organisations. Descriptive analyses and multivariable regression models will be used to examine factors related to SLNB practices and attitudes. Qualitative data will be analysed using thematic analysis. Ethics and dissemination: Ethics approval has been granted by the University of Sydney. Results will be disseminated through publications and presentations to clinicians, patients, policymakers and researchers and will inform the development of strategies for implementing SLNB guidelines in Australia.